Measurement of the plasma density in two modes of pulsed discharge burning in the penning cell - Kovtun, Yu.V.; Skibenko, A.I.; Skibenko, E.I.; Yuferov, V.B. (Вопросы атомной науки и техники, 2015)
The paper presents the experimental evidence of two modes of pulsed discharge burning in the Penning cell. The modes have different values of maximally reached plasma density and its dynamics change.